Aderência à política nacional de resíduos sólidos e análise do desenvolvimento de planos de manejo nos campi do Instituto Federal do Rio Grande do Sul - região da Serra Gaúcha - Cini, Gisele Navarini (My University, 2025)
Waste management is a significant challenge due to urban growth, industrialization, increased consumption, and population growth, combined with a lack of environmental planning. Universities, considered small urban centers, generate large amounts of waste; however, they can contribute to society by solving the problem and becoming examples of good practices. Therefore, the overall goal of this study is to analyze the extent to which IFRS [Federal Institution of Rio Grande do Sul] Campi in the Serra Gaúcha region adhere to the National Solid Waste Policy (PNRS), as well as how they can contribute to the development of solid waste management plans. To achieve that, the study followed the principles of descriptive, exploratory, and field research. Data were tabulated through quantitative and qualitative analysis, using a questionnaire with structured and semi-structured questions as the data collection instrument. The research subjects were regularly enrolled students and staff members fully engaged in their activities, as well as managers directly involved in waste management at the Campi studied. The results revealed room for improving the academic community's involvement in environmental issues and the development and implementation of the PGRS at the studied units. This was suggested by incorporating this document into the future IFRS Sustainability Policy and the PLS. Future studies addressing the challenges of developing and implementing the PGRS at the education centers, as well as identifying critical sectors, would be encouraged. The goals established in the PLS regarding this topic, combined with the incorporation of the PGRS, facilitate the visualization of an ideal waste management system model for implementation, which could serve as an example for other Campi or Federal Educational Institutes. [resumo fornecido pelo autor]
A gestão dos resíduos é um desafio significativo devido ao crescimento urbano, industrialização, aumento do consumo e crescimento populacional, combinado com a falta de planejamento ambiental. As universidades, consideradas pequenos núcleos urbanos, geram grande quantidade de resíduos, entretanto, podem contribuir com a sociedade através da solução do problema, tornando-se exemplo de boas práticas. Nesse sentido, o objetivo geral do estudo é analisar em que medida os Campi do IFRS, pertencentes à região da Serra Gaúcha, possuem aderência à Política Nacional de Resíduos Sólidos (PNRS), bem como analisar como eles podem colaborar com o desenvolvimento de planos de manejo de resíduos sólidos. Para alcançá-los, o estudo seguiu os pressupostos da pesquisa descritiva, exploratória e de campo, onde a tabulação de dados se deu por meio de análise quanti-qualitativa, sendo utilizado como instrumento de coleta de dados questionário com perguntas estruturadas e semiestruturadas, já os sujeitos da pesquisa, são alunos regularmente matriculados e servidores em pleno desenvolvimento de suas atividades, bem como gestores diretamente envolvidos na gestão dos resíduos dos Campi pesquisados. Como resultados, identificou-se que existe espaço para aprimorar o envolvimento da comunidade acadêmica nas questões ambientais, elaboração e implementação do PGRS nas unidades estudadas, por meio da sugestão de incorporar este documento na futura Política de Sustentabilidade do IFRS e no PLS. Estudos futuros relacionados às dificuldades quanto à elaboração e implementação do PGRS nas unidades, bem como identificação dos setores críticos, seriam bem-vindos. As metas estabelecidas no PLS com relação ao tema unido à incorporação do PGRS favorecem a visualização de um modelo ideal de sistema de gestão de resíduos a ser implementado, podendo servir de exemplo para outros Campi ou Institutos Federais de Ensino. [resumo fornecido pelo autor]
Keywords: Universidades e faculdades - Serra, Região (RS) - Programas de atividades; Resíduos sólidos - Brasil - Política governamental; Política ambiental - Eliminação de resíduos; Gerenciamento de resíduos; Gestão ambiental; Universities and colleges - Serra, Region (Brazil) - Activity programs; Solid waste - Brazil - Government policy; Environmental policy - Waste disposal; Waste management; Environmental management